Perancangan dan Implementasi Website Jasa Dekorasi Acara dengan Fitur Pemesanan Online di Kecamatan Muara Padang - Riski Abdoli; Apriansyah Apriansyah; Muhammad Ihsan (Jurnal Sains dan Ilmu Terapan, 2025)
The development of information technology has changed the way service-based businesses manage their operational processes, including event decoration services. Manual booking methods such as phone calls, messaging apps, or direct visits often lead to miscommunication, inefficient data management, and customer difficulties in accessing service information. In Muara Padang District, many decoration service providers still use conventional ordering methods, which are less efficient and limit business reach. This study aims to design and implement a website-based event decoration service platform with online booking features to facilitate the ordering process and improve service accessibility. The system was developed using the Waterfall method with PHP, MySQL, HTML, CSS, and JavaScript. The results show that the website successfully provides features for users to view decoration packages, make online orders, and for admins to manage orders and view transaction reports. Blackbox testing confirms that all functions work as expected. This website is expected to increase the efficiency of decoration service businesses and provide a better customer experience.